Stress analysis of finite dimensions bolted joints using the Airy stress function. (1st August 2021) - Nguyen-Hoang, M.; Becker, W.
Highlights: Stress analysis of bolted joint connections taking into account finite plate dimensions. Finite Dimensions modelled using a novel periodic arrangement technique. Good agreement with Finite Element stresses. Calculus available in handy form for quick reproduction of results. Abstract: Bolted joints are often used for the connection of safety–critical parts in the aeronautical industry. However, drilling holes also means introducing stress concentrations and precise assessment tools are essential to design both safe and lightweight optimal structures. These tools can be based on analytical means providing efficient computation. That is why the present work is dedicated to determine the stress field of finite dimensions bolted joints with isotropic plate material by means of the Airy stress function. The boundary value problem is solved by taking the stress field of the corresponding infinite domain problem and supplementing it with auxiliary functions enabling the continuous modelling of traction-free edges. The results are eventually validated against Finite Element analyses revealing good agreement.